2013
DOI: 10.1109/tmi.2013.2276060
|View full text |Cite
|
Sign up to set email alerts
|

Curl-Based Finite Element Reconstruction of the Shear Modulus Without Assuming Local Homogeneity: Time Harmonic Case

Abstract: In elasticity imaging, the shear modulus is obtained from measured tissue displacement data by solving an inverse problem based on the wave equation describing the tissue motion. In most inversion approaches, the wave equation is simplified using local homogeneity and incompressibility assumptions. This causes a loss of accuracy and therefore imaging artifacts in the resulting elasticity images. In this paper we present a new curl-based finite element method inversion technique that does not rely upon these si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 34 publications
1
33
1
Order By: Relevance
“…In our previous brain MRE simulation work it was found that inversion artifacts occurred close to interfaces between brain tissue and the FTM and ventricles. The conclusion of that earlier study was that errors at the boundaries were caused by a combination of factors: 1) reflection, refraction, and scattering at tissue boundaries leading to wave interference, which results in inversion artifacts at larger sampling steps (3 mm); 2) material heterogeneity bringing about errors in the direct inversion algorithm, which assumes local homogeneity ; and 3) averaging across the tissue boundaries due to interpolation, derivative calculations, and smoothing of the curl vector field during the inversion . However, the findings of this present study emphasize the importance of wave reflection and the resulting interference patterns, as the different wave delivery methods produce different predominant directions of motion accompanied by different magnitudes of inversion error.…”
Section: Discussioncontrasting
confidence: 53%
“…In our previous brain MRE simulation work it was found that inversion artifacts occurred close to interfaces between brain tissue and the FTM and ventricles. The conclusion of that earlier study was that errors at the boundaries were caused by a combination of factors: 1) reflection, refraction, and scattering at tissue boundaries leading to wave interference, which results in inversion artifacts at larger sampling steps (3 mm); 2) material heterogeneity bringing about errors in the direct inversion algorithm, which assumes local homogeneity ; and 3) averaging across the tissue boundaries due to interpolation, derivative calculations, and smoothing of the curl vector field during the inversion . However, the findings of this present study emphasize the importance of wave reflection and the resulting interference patterns, as the different wave delivery methods produce different predominant directions of motion accompanied by different magnitudes of inversion error.…”
Section: Discussioncontrasting
confidence: 53%
“…The current protocol includes the collection of MR elastography and mpTRUS data. Magnetic resonance elastography is performed as a part of the mpMRI procedure [51,52] and mpTRUS, which also includes TRUS elastography that is collected immediately prior to TTMB [53,54,55]. A sufficiently accurate image-based cancer detection method (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The CIRS 049 phantom had been previously used to verify MRE measurements 55, 56. In both cases different inversion approaches to the ones used here (i.e., finite element modeling) were applied; however, the recovered stiffness values were found to be lower than values reported by the manufacturer for the stiffest target and higher for the softest target.…”
Section: Discussionmentioning
confidence: 95%